The limits of olfactory perception in black vultures: a field experiment. Issue 3 (4th May 2023) - Santos, Larissa H.; Santos, Carlos D.; Da Silva, Maria L.
Abstract : New World vultures have been considerably studied regarding their sense of smell. Cathartes species present a remarkable development of their olfactory apparatus, and experiments conducted with the turkey vulture ( Cathartes aura ) demonstrated that they can locate carrion exclusively by smell at considerable distances. Black vultures ( Coragyps atratus ), because of their less developed olfactory apparatus, have been compared with the turkey vulture as a phylogenetically related species lacking the sense of smell. However, little evidence from behavioural studies supports the lack of olfaction of black vultures. We conducted a field experiment where we presented urban black vultures a binary choice of decaying fish and sand (serving as control) inside plastic bags. Birds chose the fish bait in 81% of the times they approached the plastic bags. The probability of reaction decreased significantly with the distance between the birds and the fish bait, being virtually null at 40–50 m away. Furthermore, birds clearly reacted more when the fish presented higher decaying time (7 compared to 2 days). These results show that olfaction is not only used by black vultures but is probably the most relevant sense when they search for food hidden in plastic bags and in piles of unsorted waste, which is the most common foraging environment for this species in urban areas where they are very abundant.